PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2010-2013 - Fitrya Budi Panuntun, 11.05.51.0025 (Students Journal of Economic and Management, 2015)
This study aimed to analyze the influence investment decisions, financing and dividend policy decisions contained in the financial decisions in financial management functions. Financial decisions are the most important component in determining the extent to which the management company in taking steps to maximize the value of the company, for which the financial decisions taken will affect other financial decisions and the impact on the value of the company. This study uses secondary data. The population used is an industrial manufacturing company listed on the Indonesia Stock Exchange from 2010-2013. Methods of sampling using purposive sampling technique. The variables measured in this study consisted of Investment Decision (X1), Funding Decisions (X2), Dividend Policy (X3) and Value (Y). The results showed that: Investment decisions and significant positive effect on the value of the Company. Funding decisions and significant negative effect on the value of the Company, while the dividend policy does not affect the value of the Company. Keywords: Investment Decisions, Decisions Financing, Dividend Policy and Corporate Values